Partnerstwo publiczno-prywatne jako innowacyjna forma rozwoju szkół wyższych - Kotowska-Lewińska, Monika (Wydawnictwo Naukowe UAM, 2015)
The purpose of this paper is to present a public-private partnership (PPP) as an effective and efficient public infrastructure investment model which can be successfully used by Polish universities. According to the observed world tendencies, a PPP is a solution which has recently grown in popularity among public sector institutions. An interest in this form of investment is, among other things, a consequence of the public ﬁnance crisis and a large national debt. It is also a result of the increasing needs of the society and citizens becoming increasingly conscious of their needs. Thus it has become crucial to ﬁnd new sources capable of ensuring better ﬁnancing better and a better quality of public infrastructure. The PPP model is also popular in the higher education system, especially in Western Europe, where it has been frequently used for realizing major infrastructural investments, being an example of how limited public funding for realization of educational and research projects may come in close cooperation with representatives of different sectors of industry. In the presented article, based on the concept of the public-private artnership, its origins and foreign experience in this form of investment, the chances and challenges elated with use of this model are being analyzed, with special focus on Poland and a possible use of the model by Polish universities. The Polish experience with this form of investments has also been presented. In the last part of the article, hybrid PPP projects are being discussed, both those ﬁnanced from private funds as well as those included in the Financial Perspective 2014–2020, preferred y the European Commission, the ﬁnancing of which will be secured by multimillion resources from the EU structural funds budget. It is also recommended that Polish universities should apply for those funds, but in line with the very concept of the PPP model, as a partner of private enterprises.
Public-private partnership as an innovative form of development of schools of higher education
Keywords: public-private partnership; universities; public investments ﬁ nancing